2022
DOI: 10.3389/fchem.2022.918116
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Melatonin Derivatives and the Neuroprotective Effects on Parkinson’s Disease Models of Caenorhabditis elegans

Abstract: Melatonin (MT) is a hormone with antioxidant activity secreted by the pineal gland in the human brain, which is highly efficient in scavenging free radicals and plays an important role in the neuro-immuno-endocrine system. Emerging evidence showed that MT supplementation was a potential therapeutic strategy for Parkinson’s disease (PD), which inhibits pathways associated with oxidative stress in PD. In this study, we reported a C7-selective olefination of melatonin under rhodium catalysis with the aid of PIII-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The neuroprotective effect of melatonin has been shown in many CNS diseases 27,54,55 . In this study, we found that ischemic and hypoxic states cause ER stress, leading to neural apoptosis, whereas melatonin inhibits ER stress and improves neurological function (Figure 11).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The neuroprotective effect of melatonin has been shown in many CNS diseases 27,54,55 . In this study, we found that ischemic and hypoxic states cause ER stress, leading to neural apoptosis, whereas melatonin inhibits ER stress and improves neurological function (Figure 11).…”
Section: Discussionmentioning
confidence: 64%
“…The neuroprotective effect of melatonin has been shown in many CNS diseases. 27,54,55 In this study, we found that ischemic and hypoxic states cause ER stress, leading to neural apoptosis, whereas melatonin inhibits ER stress and improves neurological function (Figure 11). In an in vitro experiment, the application of an ER stress agonist indicated that melatonin protected neurons directly from anti-ER stress.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…These compounds display an array of pharmacological activities, including antioxidant properties, neuroprotection, antithrombotic effects, angiogenesis promotion, and vascular protective capacities. [19][20][21] These attributes suggest that cinnamic acid and its analogues could serve as promising lead compounds for stroke treatment.…”
Section: Introductionmentioning
confidence: 99%